Succession Planning in Malaysian Family Owned Business– Case Studies in Malaysian Chinese Owned Business - Jade Li, Chong (2009)
Transferring a business to the next generation can pose serious challenges, especially in the SMEs sector. In many cases, the owner of the SMEs is the pillar of the company and he/she is responsible for most of the functions in the business. Some are near irreplaceable, thus, making succession even more difficult. According to research, about two-thirds of all family businesses fail to make it from the first generation to the second, and even less make it to the third. Researchers believe that the reason for this immortality is lack of planning. Predecessors do not address the issue of succession until they are forced to or when they fall sick. Based on my research with 7 family business owners in Malaysia, they all have selected their internal family member as their successor. There was no formal planning carried out in the selection of a successor. The choice is purely based on emotions and relationship. These factors are also the Chinese way of doing business, that is, depending of connections and relationships (guanxi). It is too early to tell if the ‘Malaysian way’ of succession works in the current economy/era. We need to observe longer, perhaps another 20 – 30 years to see if the second generation leaders are successful in persevering the family wealth. Family firms, especially in the SMEs sector, lacks of money and human capital. Therefore, it is important that the management of these family firms recognise this and plan strategically around such circumstances. The dynamics of the economy is changing so rapidly that the leaders in the family firms have to catch up fast!